Pancasila Sebagai Dasar Pendidikan Karakter di Era Revolusi Industri 4.0 - Andrian Sinaga; Angel L Simanjuntak; Juniarti Simamora; Desi Murni AR; Florensia Manik; Tesa Sinurat; Nurul M Azzahara; Lilis Siagian; May Hafizah; Nora Sriyanti (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Pancasila, as Indonesia's state ideology, has a crucial role in shaping the nation's character, especially in the Industrial Revolution 4.0 era which is marked by technological progress and rapid social change. This article discusses the importance of Pancasila as the basis for character education amidst the dynamics of the digital era. The integration of Pancasila values, such as divinity, humanity, unity, democracy and social justice, in the educational curriculum can form individuals who are not only competent in technology, but also have strong morality and ethics. Through a holistic approach involving schools, families and communities, as well as the use of technology as a tool for character education, it is hoped that the younger generation can adapt to changing times without losing their identity and national values. Continuous evaluation and supervision is also needed to ensure the effectiveness of implementing Pancasila-based character education. This article concludes that character education based on Pancasila is the key to facing the challenges and opportunities that arise in the Industrial Revolution 4.0 era with strong integrity and morality.